Adopsi Anak Dalam Tinjauan Madzhab Syafi'i - Abdul Halim; Khuzaimah . (MASADIR: Jurnal Hukum Islam, 2021)
Abstrak: One of the signs of happiness and family harmony is the birth of a child. Besides that, a pious child can also be an investment in the afterlife for his parents. However, not all family couples can have offspring, so there are various ways to have them. One of the ways couples have children is by adopting a child. However, not all Indonesian citizens know the correct method of adoption. How the Child Adoption And in the view of the school of shafi'i, the procedure for adoption of children can have legal consequences related to the lineage of the adopted child, the marriage guardian of the adopted child, and the inheritance status of the adopted child. Kata Kunci : Adoption, Indonesia, Madzhab Syafi'i